A multimodal analysis of ISIS’s Eid greetings video / Aasha Abdulmuhsin Ali - Aasha , Abdulmuhsin Ali (2018)
This study examines the representation of ISIS in their video Entitled “Eid Greetings from the Land of Khilafa”. Since ISIS count mainly on online means to spread their ideology and legitimize their actions, there was a need to look at how ISIS create their image by analyzing the multimodality of their videos through examining visual, verbal and textual elements, as it provides an explanation of how these elements form identities, ideologies and power. Kress and Van Leeuwen’s framework of multimodal analysis (1996) along with Machin (2016) and Ledin and Machin (2018) were utilized as an analyzing tool. The results showed that in the video ISIS presented their identity as armed Islamic group that fear no one and achieved many victories all according to Allah promise, furthermore, they encouraged the rest of Muslims to leave their houses and join Islamic state by showing the real Islamic environment in IS. In addition, they legitimize their actions by referring to Quranic verses, Hadith, and Sahaba’s sayings. The video also focused on the children as the youth of tomorrow and ISIS’s future fighters who will enable the continuity of this state.